Pengaruh Pertumbuhan Perusahaan, Keputusan Pendanaan, dan Kebijakan Dividen Terhadap Nilai Perusahaan - Al hadad, Nasrulllah; Widiyati, Dian (Jurnal Riset Rumpun Ilmu Ekonomi, 2024)
This research aims to analyze the influence of company growth, funding decisions and dividend policy on company value. This research was conducted by analyzing the financial reports of companies in the transportation and logistics sector listed on the Indonesia Stock Exchange (BEI) during the period 2018 to 2022. The sample used in this research was 9 technology sector companies listed on the Indonesia Stock Exchange during the period 2018 to 2022 using purposive sampling techniques. The data used in this research is secondary data in the form of financial reports from each company that has been used as a research sample. The variables used in this research are Company Growth (X1) as the first independent variable, Funding Decisions (X2) as the second independent variable, and Dividend Policy (X3) as the third independent variable and Company Value (Y) as the dependent variable. The panel data regression method was used as the research methodology in this study. Analysis of research results using EViews 12 Student Version Lite software. The research results show that the best model is the Fixed Effect Model (FEM). The results of this study show that partial company growth has no effect and is not significant on company value, partial funding decisions have a significant effect on company value, partial dividend policy has no effect and is not significant on company value, and simultaneously company growth and funding decisions and Dividend Policy influences Company Value.